Allegory and historical Franciscan culture in the Portuguese tiles of the Convent of San Antonio de Paraíba (Brazil, 18th century) - Oliveira, Carla Mary S. (2025)
The tile strip in the church of the Saint Anthony Convent in Paraíba, created in the 1730s, narrates the Joseph of Egypt’s saga in a continuous storyboard. This decoration reinforces the concept of a saintly life as an exemplary model, employing religious imagery as a guide for behavior, aligning with the Baroque historical culture rooted in Trento. This study delves into the allegorical and symbolic implications of the chosen theme and its treatment in the Paraíba Franciscan convent’s decoration.